ABO incompatibility in mismatched unrelated donor allogeneic hematopoietic cell transplantation for acute myeloid leukemia: A report from the acute leukemia working party of the EBMT. Issue 8 (9th June 2017) - Canaani, Jonathan; Savani, Bipin N.; Labopin, Myriam; Michallet, Mauricette; Craddock, Charles; Socié, Gerard; Volin, Lisa; Maertens, Johan A.; Crawley, Charles; Blaise, Didier; Ljungman, Per T.; Cornelissen, Jan; et al.
Abstract: ABO incompatibility is commonly observed in stem cell transplantation and its impact in this setting has been extensively investigated. HLA‐mismatched unrelated donors (MMURD) are often used as an alternative stem cell source but are associated with increased transplant related complications. Whether ABO incompatibility affects outcome in MMURD transplantation for acute myeloid leukemia (AML) patients is unknown. We evaluated 1, 013 AML patients who underwent MMURD transplantation between 2005 and 2014. Engraftment rates were comparable between ABO matched and mismatched patients, as were relapse incidence [34%; 95% confidence interval (CI), 28–39; for ABO matched vs. 36%; 95% CI, 32–40; for ABO mismatched; P = .32], and nonrelapse mortality (28%; 95% CI, 23–33; for ABO matched vs. 25%; 95% CI, 21–29; for ABO mismatched; P = .2). Three year survival was 40% for ABO matched and 43% for ABO mismatched patients ( P = .35), Leukemia free survival rates were also comparable between groups (37%; 95% CI, 32–43; for ABO matched vs. 38%; 95% CI, 33–42; for ABO mismatched; P = .87). Incidence of grade II‐IV acute graft versus host disease was marginally lower in patients with major ABO mismatching (Hazard ratio of 0.7, 95% CI, 0.5–1; P = .049]. ABO incompatibility probably has no significant clinical implications in MMURD transplantation.